Knowledge , attituds and practice of medical ethics among medical officers in three teaching hospitals in the Kandy District - Ranasinghe, A.W.I.P (My University, 2009)
This was a hospital based cross sectional descriptive study. A structured self administered questionnaire was developed and pre-tested to assess the level of knowledge, attitudes and practice of medical ethics among medical officers in three teaching hospitals in the Kandy district (n=313). Cross -analysis of selected factors and the level of knowlecge were performed to determine the association. Independent t-test and ANOVA were used tocompare mean scores on knowledge between categories. A probability value of 0.05 was considered as significant. The vast majority ( 91 percent) agreed that the undergraduate curriculum on medical ethics is not adequate and 95.3 percent of doctors justify that the inservice training on medical ethics is not adequate and 95.3 percent of doctors justify that the inservice training on medical ethics as a necessity. The vast majority of medical officers ( 81.2 percent) in three hospitals had a poor level of knowledge on medical ethics. Postgraduate trainees had comparatively a good level of knowledge than other medical officers. A mojority of medical officers had favourable attitudes towards the basic principles of beneficence and nonmaleficence. Most of the doctors frequently practiced ethically. There was no statistically significant association between level of knowledge on medical ethicas and field of work or work experience. Guidelines on ethical conduct developed by the SLMC for medical practitioners should be given and taught during the undergraduate period. In-service training programmes focused on personal professional development should be organized to improve the knowledge, attitudes and practice of medical ethics.